10 Mbps 0.3 nJ/bit OQPSK transceiver IC for 400–450 MHz medical telemetry. Issue 22 (11th October 2016) - Jiang, Hanjun; Weng, Zhaoyang; Li, Yang; Dong, Jingjing; Rhee, Woogeun; Wang, Zhihua
Abstract : A 10 Mbps OQPSK transceiver working in the 400–450 MHz frequency range is designed for medical telemetry applications requiring wireless communication with both high data rate and low power consumption. An inverter based phase‐switching transmitter has been proposed to lower the transmitter power consumption. Moreover, a digital‐assisted DC offset calibration (DCOC) technique that combines the PGA‐gain‐uncorrelated DCOC method and a lookup table is adopted to enable an zero‐IF receiver architecture. Fabricated in 65 nm CMOS process, both the transmitter and the receiver consumes ∼3 mW from 1 V supply at 10 Mbps data rate. The transceiver energy efficiency is ∼0.3 nJ/bit, which outperforms the similar designs in recent literature.